PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PELAKSANAAN PENDIDIKAN KARAKTER DI MADRASAH ALIYAH AL-FATAH PALEMBANG - Andrianto, Andrianto (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The purpose of this study was to determine the role of Islamic Religious Education teachers in the implementation of character education in Madrasah Aliyah Al-Fatah Palembang. and to find out the supporting and inhibiting factors of the role of Islamic Religious Education teachers in the implementation of character education in Madrasah Aliyah Al-Fatah Palembang. This research is a qualitative study with the type of field research, to obtain data used interview, observation, and documentation methods. The results of the research conducted by the author can be obtained information that first, the role of Islamic Religious Education teachers in the implementation of character education in MA Al-Fatah Palembang, the role of Islamic Religious Education teachers as role models, the role of Islamic Religious Education teachers as facilitators, the role of Islamic Religious Education teachers as supervisors, the role of Islamic Religious Education teachers as educators, the role of Islamic religious education teachers as motivators, the role of Islamic Religious Education teachers as mentors. Second, the supporting factors of the role of Islamic Education teachers in the implementation of character education namely, religious activities programs such as, duha prayer, zuhuhur, BTA and tahfidz, school order regulations such as, entering school and translating tasks in an orderly manner, and the attitude of teachers and students with character example. The inhibiting factors of the role of Islamic Religious Education teachers in the implementation of character education are, low facilities and infrastructure, less conducive environment, the background of each individual, lack of parents 'attention to children due to the parents' busy work.